Sistem Pendeteksi Kandungan Nutrisi dalam Tanah Berdasarkan Warna dan Kelembapan dengan Menggunakan Metode Naive Bayes - Khairul Anwar; Dahnial Syauqy; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The content of soil nutrition has its main role in the agricultural sector. farmers usually use their limited information when determining the land to be used as agricultural land. There are many farmers are experiencing the crop failure and got loss caused by mismanagement of the land. Based on these problems, a system that can detect the nutrient content in the soil which farmers will use to classify the nutrient content of the soil. This study used soil color as parameters that are obtained by using TCS3200 color sensor, while soil moisture parameters are obtained by using Soil Moisture sensor. Determination of nutritional content based on 4 parameters, there are value of R, G, B and soil moisture value of each sensor will be processed in Arduino Uno microcontroller using Naive Bayes method. The use of the Naive Bayes method refers to the decision of the nutrient content of the soil, it is known that the Naive Bayes method has a good accuracy and can be used based on class classification at the beginning of the process. Based on the test conducted on the system, it generates reading errors of the TCS3200 color sensor is 5.34% and Soil Moisture sensor error based on the reading with a humidity measuring instrument is 2.41%. Naive Bayes Method Accuracy in the classification of soil nutrition content is 100% that is obtained from 26 training datas and 13 test datas. The computing time of the system was 0.0814 seconds with 26 times test.